Exploring The Impact of Resilient Leadership on Employee and Organizational Resilience: A Systematic Literature Review - Ramadhani, Indi; Sobandi, A.; Santoso, Budi (Ann Publisher, 2024)
This study constitutes a systematic literature review to depict the evolution of resilient leadership and employee and organizational resilience and also explore the impact of resilient leadership on employee and organizational resilience. Review data included 16 studies from the literature retrieved from the Scopus database, resulting in two patterns of interaction: (1) interrelationship between resilient leadership and employee resilience and (2) interrelationship between resilient leadership and organizational resilience. Our findings suggest that resilient leadership is a key factor in achieving employee and organizational resilience.